Framework of lower-limb musculoskeletal modeling for FES control system development - Abdul Jamil, Muhammad Mahadi; Hanafi, Dirman; Ahmad, M.K.I; KSM Kader Ibrahim, Babul Salam; .Rahman, K.A.A. (Penerbit UTHM, 2015)
In recent years, the demand of interest in functional electrical stimulation (FES) is increasing due to the applications especially on spinal cord injury (SCI) patients. Numerous studies have been done to regain mobility function and for health benefits especially due to FES control development for the paralyzed person. In this paper, the existing general framework modeling methods have been reviewed and the new modeling framework approach has been discussed. In general modeling and simulation can greatly facilitate to test and tune various FES control strategies. In fact, the modeling of musculoskeletal properties in people with SCI is significantly challenging for researchers due to the complexity of the system. The complexities are due to the complex structural anatomy, complicated movement and dynamics, as well as indeterminate muscle function. Although there are some models have been developed, the complexities of the system resulting mathematical representation that have a large number of parameters which make the model identification process even more difficult. Therefore, a new approach of modeling has been presented which is comparatively less burdened compared with mathematical representations. Hence this musculoskeletal model can be used for FES control system development.